A rolling circle amplification signal-enhanced immunosensor for ultrasensitive microcystin-LR detection based on a magnetic graphene-functionalized electrode. Issue 63 (16th August 2017) - He, Zuyu; Wei, Jie; Gan, Cuifen; Liu, Weipeng; Liu, Yingju
Abstract : Construction of a rolling circle amplification signal-enhanced immunosensor for ultrasensitive microcystin-LR detection by using a magnetic graphene functionalized electrode. Abstract : A novel competitive immunosensor for the sensitive and selective detection of MC-LR was developed. Magnetic graphene was synthesized, characterized and used as the substrate to immobilize antigens onto the electrode surface due to its surface area and easy separation. Furthermore, gold nanorods were modified with polydopamine and then functionalized with a secondary-antibody and circularization DNA template. By using rolling circle amplification, the DNA template can be replicated to generate extensive repeated DNA sequences, and then hybridized with the detection probe, and thus the signal was remarkably improved. Under the optimal conditions, the proposed immunosensor showed a good linear relationship between the current response and the concentration of MC-LR in the range of 0.01–50 μg L −1 with a detection limit of 0.007 μg L −1 . The immunosensor was proved to be specific, reproducible and stable. Most importantly, the proposed biosensor was applied to detect MC-LR in a real water sample with good recovery, indicating its potential application in environmental monitoring.